PENGELOMPOKKAN HASIL SURVEI DOSEN SELAMA KEGIATAN PEMBELAJARAN DARING ( STUDI KASUS STMIK KAPUTAMA) - Hernika Nainggolan; Indah Ambarita; Siswan Syahputra (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Learning that is usually done offline is now learning at home or online using various applications such as classroom, zoom, google doc, google forms, Whatsapp groups and teacher rooms. Distance learning can reduce the risk of spreading the coronavirus and in accordance with the circular issued by the Ministry of Education and Culture for online learning. As teaching staff, lecturers are expected to continue to make efforts to improve and improve the quality of lectures through various planned programs. Lecturers are required to be able to design and design online learning that is light and effective. Lecturers are required to be able to design and design online learning that is light and effective. Thus, the implementation of online learning at STMIK Kaputama Binjai must be monitored and evaluated so that the quality of education is maintained. Evaluation of online learning can be seen from student responses or questionnaires. Thus, the implementation of online learning at STMIK Kaputama Binjai must be monitored and evaluated so that the quality of education is maintained. Evaluation of online learning can be seen from student responses or questionnaires by grouping survey results on online learning activities using the K-Means algorithm and clustering method.